Microsoft office XP volume 1 - Lauden, Kenneth C.; Rosenblatt, Kenneth; Langley, David; Pickering, Robin (Boston : McGraw-Hill/Irwin, 2002)
Computer science
Keywords: Office XP; Windows2000; Windows explorer; Word 2002; Excel 2002; Access 2002; PowerPoint 2002